Advances in Catalytic Asymmetric Dearomatization - Zheng, Chao; You, Shu-Li (ACS central science, 2021)
Asymmetric catalysis has been recognized as the most enabling strategy for accessing chiral molecules in enantioenriched forms. Catalytic asymmetric dearomatization is an emerging and dynamic research subject in asymmetric catalysis, which has received considerable attention in recent years. The direct transformations from readily available aromatic feedstocks to structurally diverse three-dimensional polycyclic molecules make catalytic asymmetric dearomatization reactions of broad interest for both organic synthesis and medicinal chemistry. However, the inherent difficulty for the disruption of aromaticity demands a large energy input during the dearomatization process, which might be incompatible with the conditions generally required by asymmetric catalysis. In this Outlook, we will discuss representative strategies and examples of catalytic asymmetric dearomatization reactions of various aromatic compounds and try to convince readers that by overcoming the above obstacles, catalytic asymmetric dearomatization reactions could advance chemical sciences in many respects.